Primary appendectomy in appendicular masses of children: an institutional experience - Puthenvariath, Jagadeesh Nelluvayil; Narayanan, Sarath Kumar; Somnath, Prathap (International Surgery Journal, 2020)
Background: Early appendectomy (EA) for appendicular mass (AM) has been found to be a safer alternative in various studies in adults, while very few studies report such advantages in pediatric population. The purpose of this study was to assess the safety, efficacy and practical implications of EA in pediatric patients with AM. Methods: All patients with acute appendicitis or its complications that underwent EA between January 2016 and December 2018 were retrospectively reviewed. AM was defined if any or combination of the following criteria were satisfied with other signs of appendicitis: palpable mass in right iliac fossa (RIF), sonologically identified mass in RIF, per-operatively confirmed as a mass by surgeon. Results: 37 patients (among a total of 642 patients) were determined to have AM per-operatively and were included in the analysis. 29.7% (n=11) had a contained appendicular abscess. Age group ranged from 4-12 years (mean 7.8 years). The key per-operative findings were fecolith (21.6%), gangrenous appendix (56.8%), difficult adhesiolysis (48.6%), and full thickness bowel injury (2.7%). Postoperatively, wound infection in 9 (24.3%), intra-abdominal abscess in 1 (2.7%), prolonged ileus in 2 (5.4%) and sepsis in 2 (5.4%) were managed medically. Conclusions: EA approach in AM is a safe option in children as it avoids misdiagnosis, treats complicated appendicitis early, avoids second admission, and has shorter hospital stay with better compliance. Failures of non-operative management and potentially lethal complications of complicated appendicitis are also eliminated.